Santa Claus conquers the Martians [videorecording (DVD)] - Webster, Nicholas; Call, John, 1915-1973; Hicks, Leonard; Beck, Vincent, 1924-1984; Zadora, Pia (Alpha Video, 2004)
Martians kidnap Santa Claus and demand that he make toys for the unhappy Martian children.